2022
DOI: 10.3390/ijerph19127438
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mental Health, Wellbeing and Flourishing in Undergraduate Students Pre- and during the COVID-19 Pandemic

Abstract: There has been a preponderance of studies on student mental health, wellbeing and flourishing during the COVID-19 pandemic. Few studies have compared data on student mental health and wellbeing before and during the pandemic. The purpose of the current study was to compare mental health and wellbeing in undergraduate students before and during the COVID-19 pandemic. Survey research was conducted with three groups of undergraduate students (n = 905) from diverse scientific fields at a large, urban university in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Therefore, COVID-19 is considered as a potential confounding variable in the study and could have negatively impacted how the participants responded to the FS. Similarly, Graham and Eloff (2022) found that college students who responded to the FS indicated experiencing a decrease in well-being before and during the pandemic. These findings are further reinforced by Nyunt et al (2021) who used the FS to assess college students’ sense of well-being, of which they responded to experiencing a significant decrease in from before and after the onset of the pandemic during the school semester.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, COVID-19 is considered as a potential confounding variable in the study and could have negatively impacted how the participants responded to the FS. Similarly, Graham and Eloff (2022) found that college students who responded to the FS indicated experiencing a decrease in well-being before and during the pandemic. These findings are further reinforced by Nyunt et al (2021) who used the FS to assess college students’ sense of well-being, of which they responded to experiencing a significant decrease in from before and after the onset of the pandemic during the school semester.…”
Section: Discussionmentioning
confidence: 89%
“…A comparison of the mental functioning of the subjects before and during the COVID-19 pandemic confirms the hypothesis of a deterioration in the subjects' emotional functioning. The experiencing of elevated levels of stress and significant deterioration in sleep quality among students are indicated by Lukowski et al [47], whereas Graham and Eloff [48] point to reduced general well-being and a deterioration of subjectively perceived mental health. In a study conducted in Brazil by Demenech et al [49], attention was paid to a statistically significant increase in the risk of suicide attempts observed among students from 2019 to 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In research with 573 students across five institutions, Diener et al (2009) found a mean FS score of 45.4 (SD = 6.2). In research with university students in South Africa, Graham and Eloff (2022) identified a significant post-pandemic decrease of 6.16 points in FS scores. However, these were comparable and not identical groups of students, and the pre-pandemic mean was 37.96, substantially lower than the scores reported in this research or by Diener et al in 2009. Unfortunately, because of absent pre-COVID comparison scores for this sample, it is impossible to draw conclusions about COVIDassociated changes to these participants in either mental health scale.…”
Section: Discussionmentioning
confidence: 99%